Phytoplankton composition, growth and production in the Guadiana estuary (SW Iberia): unraveling changes induced after dam construction - Domingues, Rita B. (2012)
Water quality and quantity problems in the Guadiana estuary due to a recently built dam have been predicted, including an enhancement of cyanobacteria blooms. The main goal of this work was thus to describe the present phytoplankton dynamics in relation to its environmental drivers and to evaluate the effects of damming on phytoplankton in the Guadiana estuary. Sampling campaigns were conducted during 2007–2009 in 4 locations of the Guadiana estuary, covering the salinity gradient. Phytoplankton-related and physical–chemical variables were analyzed. Throughout our study, light availability was mainly controlled by suspended sediments and it was much lower than saturating intensities described for phytoplankton growth. Therefore, light was probably limiting to phytoplankton growth throughout the year, especially in the middle and upper estuarine zones. Nitrogen limitation of phytoplankton growth occurred occasionally throughout the study period, especially during spring and summer. Overall, light and nutrient availability were mainly controlled by river flow; anthropogenic sources of nutrients to the estuary were negligible. Phytoplankton showed a unimodal cycle with biomass maximum in late spring/early summer, and the typical seasonal succession of freshwater phytoplankton (diatoms, green algae, cyanobacteria) was observed. Diatoms were the main component of the phytoplankton community and their variability closely followed nitrate and river flow variability. The relative abundance of the main phytoplankton groups changed in relation to the period before dam construction, with a decrease on cyanobacteria contribution to total abundance. The environmental perturbation induced by dam construction has now stabilized and resulted in an overall decrease in nutrient concentrations, an increase in light availability and a decrease in cyanobacteria abundance.